Study on connection of the Pardubice Airport to the Czech Railway Network - Jícha, Miroslav (Univerzita Pardubice, 2021)
With further developments and investments in civil aviation at the Pardubice airport, a possible railway link could be established to further ease access to the airport terminal. Sufficiently connecting an airport to other means of public transportation is of vital importance to its further development and growth in prominence. With that incentive in mind, this thesis deals with exploring whether a railway link to the airport is conceivable.
Studie napojení Pardubického letiště na českou železniční síť
Keywords: Letiště Pardubice; železnice; železniční spojení na letiště; Pardubice airport; railway; railway link to an airport